New avenues in the study of political corruption - Bull, Martin J.; Newell, James L. (Crime, law, and social change, 1997)
This article argues that the 1990s have witnessed a sea change in the study of political corruption, especially in political science. It explores the reasons for the relative neglect of corruption by political science in the past, and suggests that a process is underway whereby the study of corruption is becoming more integrated into the mainstream of the discipline. It explores the paradox of the co-existence of unresolved disputes about the definition of corruption with a consensus on the severity of the problem, suggesting that corruption remains a worthwhile object of investigation. Finally, it summarises how the contributions to this special issue light possible new avenues in the study of the phenomenon.